2022
DOI: 10.3390/cancers14174089
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of an Organized Lung Cancer Screening Program for Asbestos-Exposed Subjects

Abstract: Background: The National Lung Screening Trial (NLST) and NELSON study opened the debate on the relevance of lung cancer (LC) screening in subjects exposed to occupational respiratory carcinogens. This analysis reported the incremental cost-effectiveness ratios (ICER) of an organized LC screening program for an asbestos-exposed population. Methods: Using Markov modelization, individuals with asbestos exposure were either monitored without intervention or annual low-dose thoracic computed-tomography (LDTCT) scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Given the prevalence of asbestos exposure globally in the industrialized age and its known carcinogenic properties, it is not surprising that the screening and surveillance of asbestos-exposed populations are relatively well studied. [1][2][3][4][5][6][7][8][9] The value of screening of asbestos-exposed people by lowdose computer tomography (LDCT) of the chest has not been confirmed in randomized clinical trials, but observational studies strongly suggest that LDCT is an effective tool for early lung cancer detection. 10 Most observational studies reviewed concluded that the criteria used to select individuals for LDCT may need broadening.…”
mentioning
confidence: 99%
“…Given the prevalence of asbestos exposure globally in the industrialized age and its known carcinogenic properties, it is not surprising that the screening and surveillance of asbestos-exposed populations are relatively well studied. [1][2][3][4][5][6][7][8][9] The value of screening of asbestos-exposed people by lowdose computer tomography (LDCT) of the chest has not been confirmed in randomized clinical trials, but observational studies strongly suggest that LDCT is an effective tool for early lung cancer detection. 10 Most observational studies reviewed concluded that the criteria used to select individuals for LDCT may need broadening.…”
mentioning
confidence: 99%